Factors Affecting Teacher Performance in the Society 5.0 Era - Aradatullah Dita Illahiyah; Bujang Rahman; Handoko; Siti Rahma Sari (Journal of Educational Management Research, 2026)
This study aims to examine the influence of transformational leadership, self-efficacy, entrepreneurial character, and organizational culture on teacher performance in the context of the Society 5.0 era. The study employed a literature review approach by systematically analyzing and synthesizing findings from 25 relevant scholarly articles obtained from reputable academic databases and publications. The reviewed literature was selected based on its relevance to teacher performance and the factors that contribute to educational effectiveness in a technology-driven environment. The findings indicate that transformational leadership plays a significant role in enhancing teachers’ motivation, adaptability, and innovation in instructional practices. Self-efficacy contributes to teachers’ confidence in managing learning activities and addressing educational challenges. Entrepreneurial character encourages creativity, initiative, and problem-solving skills, while a supportive organizational culture fosters collaboration, professionalism, and continuous improvement. Collectively, these factors contribute positively to improving teacher performance and readiness to meet the demands of modern education. The study implies that educational institutions should strengthen leadership practices, promote teacher self-efficacy, cultivate entrepreneurial values, and develop a positive organizational culture to enhance teacher performance and support sustainable educational development in the Society 5.0 era.